Considerações sobre o uso das TICs (Tecnologias de Informação e Comunicação) na prática docente em Artes Visuais na Rede Municipal de São Luís-MA - Lima, Weeslem Costa de (2016)
Experiences built, while teaching in the municipal education in São Luís - MA, inclined us to know the technologies used by the students of the municipal system of the city and especially the applications of it in the methodologies of the teachers of discipline of Arts. Through this, we propose to investigate, in 2015 to the first half of 2016, the use of ICT (Information and Communication Technologies) in teaching practice in Visual Arts in the city of São Luís - Maranhão – SEMED. The research, in a descriptive approach, aimed to know and verify the performance of teachers, constituting from quantitative and qualitative data. We center our attention on 21 teachers of the middle school, stage related to the 6th, 7th, 8th and 9th grades, which it is incumbent upon the municipal school system. In the development, we seek to draw a research methodology which included literature, questionnaires and interviews. Tools such as email, Facebook and WhatsApp were indispensable for obtaining information. The theoretical support is composed of Ferraz & Fusari (1993), authors that focus on historical aspects of art education in Brazil, the articulation of the pedagogical trends and the reflection on the performance of teachers. Dermeval Saviani (2008) discusses the education in Brazil, in the historical perspective and aimed to the pedagogical practices of teachers. His views are placed together with other theorists so we can think technological aspects as an educational resource. Vani Moreira Kenski (2007) and José Manuel Morán Costa (1993) establish issues related to technology in the educational environment. Lucia Gouvêa Pimentel (2007) and Philippe Perrenoud (2000) have their thoughts on teacher training in the teaching of art and the use of the contemporary technologies punctuated in the research. In addition to these theoretical and conceptual references, documents which focus on the technologies are used, official texts and relevant documents for the teaching of the discipline. We believe that the reflective and continuing reconstruction exercise, provided by the research can aid understanding of an educational discipline and approach the competent elements of the results, needs and discussions that permeate this universe.